Depression symptoms and suicide risk of internal medicine residents before and after first year of the COVID-19 pandemic - De La Roca-Chiapas, Jose Maria; Grajeda Gutiérrez, Carlos Francisco; Íñiguez Venegas, Valeria Judith; Hernández González, Martha Alicia; Reyes Pérez, Verónica (Frontiers in Psychology, 2023)
Objectives: Investigate the association between depressive disorder and suicide risk with elevated levels of serum cholesterol and low levels of serum cortisol among internal medicine residents in a specialist medical hospital in Leon, Guanajuato, Mexico, before and after COVID-19. Methods: It’s a longitudinal study. Internal medicine residents were initially monitored for two months before starting to care for patients with COVID-19. Participants were asked to fill out depression and suicide risk surveys, we measured the serum cholesterol and cortisol of each participant, and again after 11 months of attending to COVID-19 patients. The Plutchik survey of depression and suicide risk was applied. In addition, the cholesterol and serum cortisol of residents of the specialist internal medicine of the second, third, and fourth years of UMAE-IMSS. Results: We found a significant correlation between serum cholesterol levels and suicide risk (r=0.366, p<0.01), we also found differences in serum cortisol levels (=3.189, p<0.01) and cholesterol (t=4.3, p<0.0001) before and after the pandemic. Conclusions: Caring for patients with COVID-19 in the hospital contributed to an increase in levels of depression and suicidal ideation, as well as differences in levels of cortisol and cholesterol in resident physicians of internal medicine, among the possible reasons for this change could be the conditions of personal protection while attending to patients, the uncertainty in the first months of not knowing how the virus was transmitted and not having or knowing when they would be vaccinated, as well as the lack of a strategy of adequate mental health support from the institutions dedicated to their academic training.